Experiences of establishing and managing 'artist-run' exhibition spaces in Dublin, from 2005 to 2015. - MURPHY, ALEXANDRA (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2019)
This thesis explores the phenomenon of visual arts exhibition organisations known as 'artist-run spaces' in Dublin, from 2005 to 2015. This marks a period of unprecedented growth of the phenomenon, followed by a rapid decline. Through in-depth interviews the experiences of some of the individuals who were involved in running these organisations are documented and analysed. This provides an intimate insight into the organisations, through which their modus operandi is revealed. Key areas of investigation include why the organisations are established, their activities, their governance and management structures, and how they are financed. The research reveals that these organisations provide access to studio facilities and vital opportunities for artists to exhibit. There is also evidence to suggest that they play an important role in supporting artists in developing and refining their professional practice. Thus, they make an important contribution to the Irish arts infrastructure. However, the organisations are sometimes compromised by inexperienced management, excessive workloads, insecure tenancies, poor financial sustainability, and they do not always provide adequate supports to artists. The personal accounts of interviewees provides a unique insight into the reasons why the organisations developed in the form that they did and of the achievements and challenges experienced in this journey. Additional interviews with some artists that exhibited with these organisations provides a counter narrative through which these accounts are both supported and critiqued. This thesis provides unprecedented insight into these organisations which contribute to the delivery of arts in Dublin within this recent context.
APPROVED
Keywords: artist studio facilities, Dublin; arts administration and management; support for artists, Dublin